Risk Factors Associated with Elderly Diabetes Patients - Khuluq, Husnul; Fitri, Dwiki; Miyarso, Condrosuro; Winarno, tunjung (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Diabetes mellitus is a chronic disease with increasing global prevalence, including in Indonesia. Among the elderly, its management is more complex due to age-related physiological changes and comorbidities. This study aimed to identify and analyze risk factors associated with diabetes in the elderly population. Subjects and Method: This retrospective cross-sectional study analyzed medical records of 1,634 inpatients with type 2 diabetes mellitus at PKU Muhammadiyah Hospital Yogyakarta from January 2021 to July 2023. Total sampling was used. Data on demographics, comorbidities, and laboratory values were analyzed using Chi-square test. Results: Of 1,634 patients, 853 (52.52%) were aged >65 years. Significant risk factors associated with elderly diabetes included elevated erythrocytes (OR= 1.60; 95% CI= 1.32–1.96; p <0.001), urea (OR= 1.51; 95% CI= 1.23–1.86; p <0.001), lymphocytes (OR= 1.26; 95% CI = 1.04–1.53; p= 0.020), hemoglobin (OR= 1.38; 95% CI = 1.14–1.68; p <0.001), systolic blood pressure (OR= 1.33; 95% CI= 1.07–1.65; p= 0.009), stroke (OR= 1.59; 95% CI = 1.09–2.32; p= 0.016), creatinine (OR= 1.24; 95% CI= 1.02–1.51; p= 0.028), and hypertension (OR= 1.29; 95% CI = 1.03–1.63; p= 0.028). Conversely, cholesterol (OR= 0.89; 95% CI= 0.65–1.23; p<0.001), and glucose (OR= 0.65; 95% CI= 0.51–0.83; p <0.001) were inversely associated. Conclusion: Elderly diabetes is significantly associated with multiple clinical and laboratory indicators. These findings highlight the importance of comprehensive monitoring to improve elderly diabetes management.